From concession to administrative authorization: a necessary reform to the access regime for the provision of public postal service in Peru - Vásquez, Piero Amadeus Rojas (Universidad Nacional del Litoral, 2021)
According to the Peruvian legal framework, postal service is an economic activity that has a public interest, open to competition and market standards to the point that, to date, there are more than 600 postal operators. However, in order to access the provision of the above mentioned service, previously it is necessary to obtain a concession, a legal institution that is typically granted for monopolized activities, in markets that impose restrictions for the free access by individuals. Hence, this work proposes the legal possibility that the provision of the postal public service is carried out through an administrative authorization, instead of a concession, as it happens in the European Union.